2010
DOI: 10.1007/s12040-010-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation to characterise soil macroporosity under different land use and land covers of northeast India

Abstract: Saturated macropore flow is the dominant hydrological process in tropical and subtropical hilly watersheds of northeast India. The process of infiltration into saturated macroporous soils is primarily controlled by size, network, density, connectivity, saturation of surrounding soil matrix, and depthwise distribution of macropores. To understand the effects of local land use, land cover and management practices on soil macroporosity, colour dye infiltration experiments were conducted with ten soil columns (25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…The developed model framework is based on the physical processes on the hillslopes, where topmost surface layer interacts with the rainfall. At a hillslope site, surface runoff can be generated by any of three (1) infiltration excess; (2) saturation excess; or (3) variable source area processes [4]. If the soil is saturated, then saturation excess overland flow or retention excess flow occurs from the vegetated hillslope areas and the agriculture fields, most common near the toe of the slopes where the accumulated water from the entire hillslopes is enormous in volume [30].…”
Section: Hydrological Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed model framework is based on the physical processes on the hillslopes, where topmost surface layer interacts with the rainfall. At a hillslope site, surface runoff can be generated by any of three (1) infiltration excess; (2) saturation excess; or (3) variable source area processes [4]. If the soil is saturated, then saturation excess overland flow or retention excess flow occurs from the vegetated hillslope areas and the agriculture fields, most common near the toe of the slopes where the accumulated water from the entire hillslopes is enormous in volume [30].…”
Section: Hydrological Modelingmentioning
confidence: 99%
“…It is important to quantify soil macroporosity and trace the dominating flow paths within continuous soil macropores to interpret the underlying flow mechanisms. The experimentally-derived quantitative data of soil macroporosity can have wide range of applications in various study domains such as water quality monitoring and groundwater pollution assessment due to preferential leaching of solutes and pesticides, study of soil structural properties and infiltration behavior of soils, investigation of flash floods in rivers, and hydrological modelling of the watersheds [4]. To understand the flow behavior of infiltrated water in active macropore structures of saturated undisturbed soil columns, dye tracing experiments and subsequent digital image processing exercises were carried out for the experimental plot in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Soil bulk density and saturated hydraulic conductivity of homogeneous soil matrix were in the range of 1.095-1.245 g/cc and 37-70 mm/h, respectively. Dye staining experiments conducted with the soil samples of the experimental plot indicated the presence of dense and well connected network of small diameter (1-2 mm) soil macropores (Shougrakpam et al, 2010). Therefore, very high infiltration rate, predominantly through the preferential pathways of the hillslope soil, was anticipated (Sarkar et al, 2008b).…”
Section: Description Of the Hillslope Plotmentioning
confidence: 99%
“…For example, several studies reported that land use change from natural vegetation to agricultural lands increased overland flow during the rainy monsoon phase and reduced baseflow during the dry phase in this region (Bewket and Sterk, 2005;Feoli et al, 2002;Taddese, 2001;Zeleke, 2000). In other countries as well, clearing of forests resulted in decreased infiltration rates and lower percolation to the sub-soils (Hanson et al, 2004;Mendoza and Steenhuis, 2002;Nyberg et al, 2012;Shougrakpam et al, 2010). Identification of the dominant runoff mechanism in relation to not only topography but also land use in the Ethiopian highlands is therefore essential for the development of effective soil and water conservation methods in this region.…”
Section: Introductionmentioning
confidence: 99%